Geographic variation and acclimation effects on thermoregulation behavior in the widespread lizard Liolaemus pictus. (January 2017) - Artacho, Paulina; Saravia, Julia; Perret, Samuel; Bartheld, José Luis; Le Galliard, Jean-François
Abstract: Populations at the warm range margins of the species distribution may be at the greatest risks of extinction from global warming unless they can tolerate extreme environmental conditions. Yet, some studies suggest that the thermal behavior of some lizard species is evolutionarily rigid. During two successive years, we compared the thermal biology of two populations of Liolaemus pictus living at the northern (warmer) and one population living at the southern (colder) range limits, thus spanning an 800 km latitudinal distance. Populations at the two range margins belong to two deeply divergent evolutionary clades. We quantified field body temperatures (Tb ), laboratory preferred body temperatures (PBT), and used operative temperature data (Te ) to calculate the effectiveness of thermoregulation ( E ). During one year in all populations, we further exposed half of the lizards to a cold or a hot acclimation treatment to test for plasticity in the thermal behavior. The environment at the southern range limit was characterized by cooler weather and lower Te . Despite that, females had higher Tb and both males and females had higher PBT in the southernmost population (or clade) than in the northernmost populations. Acclimation to cold conditions led to higher PBT in all populations suggesting that plastic responses to thermal conditions, instead of evolutionary history, may contribute to geographic variation. Lizards regulated moderately well their body temperature ( E≈ 0.7): they avoided warm microhabitats in the northern range but capitalized on warm microhabitats in the southern range. We review literature data to show that Liolaemus species increase their thermoregulation efficiency in thermally challenging environments. Altogether, this indicates that habitats of low thermal quality generally select against thermoconformity in these lizards. Highlights: Variation in thermoregulation behavior between range margins is rarely investigated. Liolaemus lizards from the cold margin preferred higher body temperatures. Thermal acclimation may contribute to this counter-gradient temperature variation. Selection for faster life cycle in a colder environment may explain the geographic variation.